Physiological Responses of Selected Blood VariablesAccompanying a Plyometric Training Program in YoungTennis Players - Dr. Hussein Ali Hussein Al-Kufi (Proximus Journal Publishing, 2026)
The main purpose of this study is to identify the effect of a plyometric training program on specific physical performance metrics and to detect the physiological reactions of specific blood variables. one-group pre-test and post-test designed and used in the experimental method of the current research. The sample of the research consisted of 16 young tennis players, aged between 15 to 16. The plyometric training regimen was implemented for (8) weeks, with (3) training sessions every week. In addition to explosive power and sprint speed, blood indicators (hemoglobin, creatinine, and urea) were also evaluated. The results showed statistically significant differences in favor of the post-test for all studied variables, indicating positive physiological adaptations resulting from the plyometric training program. According to the study's findings, plyometric exercise helps young tennis players perform better physically and improve a few physiological blood indicators
Keywords: Plyometric training; Physiological responses; Hemoglobin; Creatinine